Capital structure manufacturing companies in Indonesia: In review - Trisninik Ratih Wulandari; Doddy Setiawan (University of Merdeka Malang, 2020)
This study aims to provide an in-depth overview of the selection of capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2017. The data of this study were 127 annual reports of manufacturing companies listed on the IDX, divided into three types of industry, namely basic and chemical industries, miscellaneous industries, and consumer good industries. The capital structure ratios used in this study were Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER). It also looked at the ratio of Current Liabilities to Total Debt (CL/TD) and the ratio of Long Term Debt to Total Debt (LTD/TD). The results showed the average DAR of manufacturing companies in Indonesia for 3 years was 45 percent. Meanwhile, the DER rate was 111 percent. The debt of manufacturing companies in Indonesia was dominated by current liabilities compared to long-term debt. The consumer good industries had the lowest DAR and DER levels compared to basic and chemical industries and miscellaneous industries. This study can be used as a basis and overview of the capital structure of manufacturing companies listed on the Stock Exchange for further studies. JEL Classification: G32, L60DOI: https://doi.org/10.26905/jkdp.v24i4.4312